Transformation Model of History Learning in Increasing Student Competency - Laila, ST. Noer Farida; Anwar, Heru Syaiful (Al-Hayat: Journal of Islamic Education, 2024)
Since Islamic boarding school-based madrasas maintain books as a source of history learning, teachers face serious challenges, form students' critical and chronological thinking skills through book study. This encourages a transformation of history learning, which has been taking place traditionally. This study aims to explore and describe book-based history teaching and learning to improve student competence. This research is qualitative, using a case study type. Data collection techniques use interviews, observation and documentation. Data is analyzed using relevant theories or previous research findings. Data validity is carried out by extending observations. This study found that book-based history learning was transformed by formulating personal-social goals without ignoring transformative goals, emphasizing a chronological approach in education, and developing CRI (Constructed Response Items) model evaluation questions. Book-based learning activities are different from using modern textbooks. Teachers' creative and innovative efforts are needed to realise learning objectives in madrasas through book learning. Apart from mastering the content, the national curriculum is also directed at developing critical, creative, communicative, collaborative and literacy skills.